The Relationship Between Knowledge and Compliance with Blood Supplement Tablets Consumption in Adolescents at SMAN 1 Seyegan - Intan Nur Aulia Dewi; Dewi Rokhanawati (Viva Medika, 2024)
Background: Globally, anemia remains a significant issue in the health sector. In 2013, the prevalence of anemia among adolescent girls was approximately 37.1%, which increased to 48.9% in 2018. Objectives: This study aims to identify the correlation between the knowledge of adolescent girls and their compliance with consuming iron tablets at SMAN 1 Seyegan. Methods: A quantitative method with a cross-sectional approach was chosen for this study. Random sampling was used for sample collection, and data analysis was conducted using the Chi-Square test. Results: The Chi-Square test analysis yielded a p-value of 0.000 (p<0.05) and a Contingency Coefficient of 0.561, indicating a moderate relationship between the two variables. Conclusion and Recommendations: A correlation between adolescent girls' knowledge and compliance with consuming iron tablets at SMAN 1 Seyegan has been identified. It is recommended that knowledge about anemia and compliance with iron tablet consumption be enhanced